Investigation of electronic and chemical sensitization effects promoted by Pt and Pd nanoparticles on single-crystalline SnO nanobelt-based gas sensors - Barbosa, Martin S. [UNESP]; Suman, Pedro H. [UNESP]; Kim, Jae J.; Tuller, Harry L.; Orlandi, Marcelo O. [UNESP] (Elsevier B.V., 2019)
This work reports on the gas sensor response of undecorated 1D stannous oxide nanobelts and those decorated with Pt and Pd nanoparticles. The sensor device responses to H-2, CO and NO2 were measured in dry air baseline atmosphere as functions of the analyte concentration (1-1000 ppm) and temperature (100-350 degrees C). Noble metal decorated SnO devices exhibited enhanced chemical sensitization, resulting in increased sensitivity upon exposure to reducing gases at different working temperatures. Differences in enhancement levels are attributed to strong electronic sensitization effects that are dependent on the respective Pt and Pd work functions and the unique SnO band structure, characterized by a small band gap. Gas sensing results also showed superior selectivity to H-2 for metal-decorated nanobelts. Based on the findings in this work, we propose an array based on SnO structures capable of detecting and distinguishing reducing and oxidizing gases.
Keywords: Gas sensors; SnO; Nanobelts; Catalysis; Surface sensitization; Pt; Pd